Enumeration and molecular detection of Bacillus cereus in local indigenous and imported rice grains - Bilung, Lesley Maurice; Tahar, Ahmad Syatir; Tan, Pei Shze; Jamie, Samantha Valarie Furzanne; Hashim, Hashimatul Fatma; Apun, Kasing; Radu, Son (BioMed Central, 2016)
Background: Bacillus cereus is frequently related to foodborne illness outbreak. The common food vehicles for transmission of the bacteria are rice, rice products and starchy foods. As rice is a staple food for some countries including Malaysia, knowledge about safety of B. cereus in rice is important. This study was conducted to enumerate and identify B. cereus in local indigenous and imported rice grains. As Malaysia depends on imported rice to complement the food demands, it is crucial to assess on the imported rice besides the locals.